Risk factors and metabolic control degree in diabetic patients older than 8 years - Antonio Masot Rangel; Dinorah Janet Torres Lugo; Iván Castillo Ledo; Silvia Janet Masot Torres; Laura Vazquez Pis; Iriam Rojas Díaz (Medisur)
Foundation: Type 1 diabetes mellitus is one of the most common chronic diseases in childhood. The progressively longer survival of diabetic children is associated with an increase in the prevalence of complications. Their metabolic control prevents acute and chronic complications. Objective: to determine the behavior of risk factors and the degree of metabolic control in diabetic patients older than 8 years. Methods: A descriptive study was carried out at the Paquito González Cueto Hospital in Cienfuegos, between September 2021 and September 2022. The sample consisted of 74 patients over 8 years of age, taken from the universe of 103 pediatric patients diagnosed as diabetic in the province. The studied variables were: sex, age, nutritional assessment, Tanner stage, time of disease evolution, symptoms of decompensation, cholesterol value, glycemia value, glycosylated hemoglobin value and metabolic control. Results: The female sex predominated (56.7%), patients in the age group of 11-14 years (56.8%) and normal weight (70.3%). The most observed range of disease evolution was 1-4 years (59.5%). Delayed pubertal development was present in 20.2% of cases. All patients had cholesterol levels below 6.5 mmol/l (100%). Glycosylated hemoglobin was in the range of 6.6-10% in 64.9%. Inadequate metabolic control was identified in 83.8% of cases. Conclusions: Adequate metabolic control guarantees normal blood sugar and cholesterol levels. More than 50% of the patients analyzed were of normal weight and had no associated risk factors.